Reorientasi Jurusan Manajemen Pendidikan Islam (MPI) Antara Tenaga Kependidikan dan Tenaga Pendidik - M. Misbah (Cendekia: Kependidikan dan Kemasyarakatan, 2018)
Abstrak: This article discusses the problems faced by the majority of students MPI FTIK IAIN Purwokerto. On the one hand, there is the desire of MPI students to become educators, and on the other hand according to the Department, they are oriented to become educational personnel. The study focused on curriculum content and policy of MPI Department of FTIK IAIN Purwokerto. With the method of unstructured in-depth interview, documentation, moderate participant observation and data analysis, it is found that the orientation of MPI Department is based on the vision, the mission stated in the profession to be achieved that is the main profession and the alternative profession. To support the orientation of the Department of MPI, the scientific core of MPI in the curriculum of the Department which becomes its distinguishing character is related to the science MPI contained in the MPI 001 to MPI 025 course code. The way of Department in socializing the orientation of the Department as well as construct the orientation of students to fit the orientation of the Department is through Introduction Academic Orientation activities, provision of Academic Guidebook, Maximization of Role of PA, Prodi, HMPS / HMJ, MPI Department profile viewing on IAIN Purwokerto website.ملخص: درس هذا المقال المشاكل التي يواجهها طلاب قسم إدارة التربية الإسلامية في كلية التربية والعلومالتعليمية بالجامعة الإسلامية الحكومية فورووكيرتو. ثمة إرادة من طلاب هذا القسم لأن يكونوا مدرّسين ،وفي جانب آخر أن يكونوا موظفّين تربويين. تُركزُ الدراسة في محتوى المنهج وقرارات كلية التربية والعلومالتعليمية في هذه الجامعة. تجمع البيانات عن طريق المقابلة غير التركيبية، والوثائق المكتوبة، والملاحظةبشبه المشاركة، وبعد التحليل حصل الباحث على نتائج البحث هي أن اتّاه قسم إدارة التربية الإسلاميةمناسب برؤيته ورسالته المتمثّلتان في المهنة التي حاول الطلاب الحصول عليها، هي المهنة الأساسية والمهنةالاختيارية. ولدعم اتجاه القسم، فإن فئة العلوم لهذا القسم في المنهج التميّزى هي العلوم المتعلقة بإدارة التربيةوالطريقة التى اتّذها . MPI 0025 – MPI الإسلامية وهي مكتوبة في رموز المواد الدراسية من 001القسم للتعريف بهذا الاتجاه وفي نفس الوقت تكوين اتجاه الطلاب ليكون اتجاههم مناسبا باتجاه القسم،هي عن طريق التعريف الأكاديميّ، توزيع كتاب الإرشاد الأكاديمي، تعزيز وتقوية دور المشرف الأكاديمي من قبل المحاضرين، والقسم، ومنظّمات الطلبة في القسم والكلية، والتعريف بقسم إدارة التربية الإسلاميةعن طريق الموقع للجامعة الإسلامية الحكومية فورووكيرتو في الانترنت.